Exhaled and Nasal Nitric Oxide - Impact for Allergic Rhinitis - Antošová, Martina; Benčová, Alica; Mokrá, Daniela; Plevková, Jana; Pepucha, Ľubomír; Buday, Tomáš (Physiological research, 2020)
FeNO measurement is a validated non-invasive technique, which is used for diagnosis and monitoring of asthma. It would be desirable to find a reliable method to monitor allergic rhinitis (AR) via measurement of FeNO, and/or nasal nitric oxide (nNO). The aim of our study was the assessment of the efficacy of FeNO and nNO as markers in AR treatment. FeNO and nNO were measured with the portable NO analyser (NIOX MINO®) in healthy participants and in patients with AR. The patients were examined during the pollen season and out of it. The effect of local corticosteroids and antihistamine therapy was observed in patients with AR during pollen season after three weeks of therapy. There are significant differences between FeNO and nNO in patients with AR compared to healthy controls at all set points of measurements. While FeNO responded well to the treatment with both antihistamines and combined therapy, nNO decreased only after combined therapy with antihistamines and nasal corticosteroids. nNO monitoring alone is not a suitable method to monitor inflammation of the upper airways in AR and its suppression by anti-allergic treatment and should be correlated with other markers as FeNO or symptom scores.
Keywords: Young Adult; alergická rýma; Nitric Oxide; Male; biologické markery; Nasal Mucosa; mladý dospělý; Biomarkers; Adolescent; hormony kůry nadledvin; Adult; dospělí; oxid dusnatý; mužské pohlaví; Histamine Antagonists; nosní sliznice; mladiství; Rhinitis, Allergic; Administration, Intranasal; lidé; ženské pohlaví; vydechnutí; Humans; Adrenal Cortex Hormones; aplikace intranazální; Female; lidé středního věku; Exhalation; antihistaminika; Middle Aged